Assessing the Mitigation Potential of Environmental Impacts From Circular Economy Strategies on an Industrial Sector and Its Value Chain: A Case Study on the Steel Value Chain in Quebec - Binet, Flavien; Saunier, François; Margni, Manuele (Frontiers in Sustainability, 2021)
This research project aims to evaluate the potential reduction of environmental impacts from circular economy strategies on an industrial sector at a regional scale with a case study on GHG emissions in Quebec’s steel industry and its value chain. To do so, an integrated model has been created based on the matrix approach, building on material flow analysis (MFA) tracking flows and stocks and on life cycle assessment (LCA) to compute direct (from the activity, e.g. combustion process) and indirect (from supply chain, e.g. production of raw material inside or outside of region) emissions. This theoretical model is designed to be applied to any emissions or environmental impacts from a specific sector in a given region, and enable to model the effects of circularity strategies to both flows and related environmental impacts. The overall mitigation potential of individual or combined circular economy strategies on a specific sector could thus be evaluated across its entire value chain. In the case study, a set of the most promising circular strategies applicable in the Quebec context were identified and the GHG reduction potential within and outside the province is calculated and compared to actual emissions. Six circular strategies were analyzed acting at three different levers: GHG/material (increase iron recycling rate, switch to hydrogen-based reduction production), material/product (reduce weight of vehicle, limit overspecification in building construction), product/service (increase buildings and cars lifetime, increase car-sharing) and therefore impact rather direct or indirect emissions on different stages of the steel life cycle. Combining these six strategies into a consolidated scenario shows that a circular driven economy allows to cut down GHG emissions of the cradle-to-gate steel industry value chain by -55%, i.e., 1.67 Mt CO2e. Taking into account use phase of steel, overall reductions are estimated at -6.03 MtCO2e, i.e., -30% of the whole life cycle.